Differentiating vestibular migraine from Meniere's disease: an analysis of clinical features, videonystagmography, and caloric testing - Zhang, Xueyan; Wang, Qirong; Xu, Jiao; Zhou, Tao; Xu, Jin; Liu, Zheng; Yang, Xu; Cai, Huaying; Luo, Wencheng; Hu, Mei; Chang, Liying (Frontiers in Neuroscience, 2026)
ObjectiveVestibular migraine (VM) and Meniere's disease (MD) are episodic vertigo disorders with overlapping symptoms, often leading to misdiagnosis. This study aimed to identify a cost-effective diagnostic method to distinguish VM and MD.MethodsIn this retrospective study, 108 VM patients and 65 MD patients were enrolled. Clinical symptoms, interictal videonystagmography (VNG) findings, and caloric test results were analyzed and compared between the two groups.ResultsThe VM group had a significantly higher proportion of females (p < 0.001). No significant differences were observed in any features of interictal nystagmus, including spontaneous or positional nystagmus (all p > 0.05). However, the caloric test revealed a significantly higher proportion of canal paresis (CP) in MD patients compared to VM patients (p < 0.001).ConclusionWhile clinical symptom profiles effectively distinguish VM from MD, interictal nystagmus analysis has limited diagnostic value. The caloric test is a reliable and practical tool, as the presence of significant canal paresis strongly indicates MD over VM. Combining symptom evaluation with caloric testing offers a cost-effective strategy for the differential diagnosis of these common vestibular disorders.